Salicylic Acid Concentrations Suppress Grey Mold in Tomato Plants - Waheed , A. Q.; Dewan H. M.; Abdulla , M. I. (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Grey mold caused by Botrytis cinerea severely constrains tomato production in greenhouse and field systems worldwide.Specific Background: Chemical fungicides often fail due to the pathogen’s genetic plasticity, prompting exploration of alternative resistance inducers such as salicylic acid (SA).Knowledge Gap: Limited data exist regarding concentration-dependent responses of SA against B. cinerea under combined laboratory and greenhouse conditions.Aim: This study evaluated six SA concentrations (0–10 mM) for their ability to suppress fungal growth and reduce lesion development on tomato leaves.Results: Concentrations of 8 and 10 mM completely inhibited mycelial growth and biomass production (0.0 mg; 100% inhibition) in vitro. Under greenhouse conditions, the same concentrations reduced lesion area to 0.0 mm at 24, 48, and 72 hours compared with the untreated control. Lower concentrations produced partial suppression in a dose-dependent manner.Novelty: The findings demonstrate a clear concentration threshold at 8 mM SA for complete fungal suppression across experimental systems.Implications: SA presents a promising eco-compatible strategy for grey mold management and may serve as a complementary tool within integrated disease control programs. Highlights: 8–10 mM SA achieved complete fungal growth suppression. Biomass dry weight reduced to 0.0 mg under optimal concentration. Greenhouse lesion development eliminated at threshold dose. Keywords: Salicylic Acid, Botrytis Cinerea, Tomato, Grey Mold, Induced Resistance